ANALYSIS OF LOAN TO DEPOSIT RATIO DETERMINANTS OF CONVENTIONAL BANKING IN INDONESIA IN 2024 - Nubatonis, Marcellinus Manek (Universitas Dharmawangsa Medan, 2025)
This study aims to analyze the effect of Third-Party Funds (DPK) and Lending Interest Rates on the Loan to Deposit Ratio (LDR) of conventional banks in Indonesia in 2024. This research employs a quantitative method with an explanatory approach. The data used are secondary data obtained from the monthly financial reports of the five largest conventional banks in Indonesia (Bank Mandiri, BNI, BCA, BRI, and BTN), published by the Financial Services Authority (OJK). The analysis was conducted using panel data regression with the Random Effect Model (REM). The results show that Third-Party Funds (DPK) and Lending Interest Rates simultaneously affect the LDR. Partially, DPK has a positive and significant effect on the LDR, while the Lending Interest Rate has a negative and significant effect. These findings indicate that an increase in DPK encourages credit growth and raises the LDR, while higher lending rates tend to reduce credit demand. The study highlights the importance of effective fund management and interest rate policy in maintaining the balance between bank liquidity and credit distribution.